Advances in Cancer Survivorship Management - Foxhall, Lewis E.; Rodriguez, Maria Alma (MD Anderson Cancer Care Series, 2015)
This volume presents the MD Anderson experience in providing care and services to the rapidly growing population of cancer survivors, which is currently estimated to be 12 million in the United States and more than 25 million worldwide. As cancer survival rates have increased, it has slowly become clear that the challenges faced by people with cancer do not end with treatment but simply change. This book aims to assist community oncologists, physicians, and their staff, who care for the vast majority of cancer survivors, by disseminating models of surveillance for disease recurrence, screening for second primary cancers, education regarding potential late effects of treatment, and psychosocial counseling. These models have proven valuable to cancer survivors who receive care at MD Anderson.